2015
DOI: 10.1016/j.scog.2015.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting work outcome in Japanese patients with schizophrenia: role of multiple functioning levels

Abstract: Functional outcomes in individuals with schizophrenia suggest recovery of cognitive, everyday, and social functioning. Specifically improvement of work status is considered to be most important for their independent living and self-efficacy. The main purposes of the present study were 1) to identify which outcome factors predict occupational functioning, quantified as work hours, and 2) to provide cut-offs on the scales for those factors to attain better work status. Forty-five Japanese patients with schizophr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…To our knowledge, there has been no attempt to elucidate the effect of tDCS on this level of functional outcomes in psychiatric conditions. In view of the association between performance on the UPSA-B and real-world functional outcomes ( 43 ), the result reported here suggests the ability of tDCS to enhance social outcome in schizophrenia.…”
Section: Discussionmentioning
confidence: 61%
“…To our knowledge, there has been no attempt to elucidate the effect of tDCS on this level of functional outcomes in psychiatric conditions. In view of the association between performance on the UPSA-B and real-world functional outcomes ( 43 ), the result reported here suggests the ability of tDCS to enhance social outcome in schizophrenia.…”
Section: Discussionmentioning
confidence: 61%
“…On the other hand, the SFS has 7 domains and assigns points to items on each domain. The sum of these domain scores provides the total score of social functioning [21,22]. …”
Section: Discussionmentioning
confidence: 99%
“…Finally, Harvey et al [47] suggested that self-reporting is a problematic way to assess functioning, because patients with schizophrenia often show a reduced awareness of their psychotic symptoms. On the other hand, Sumiyoshi et al [22] reported that patients' SFS data are highly correlated with informants' data and with informant-based objective measures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although those “gold-standard” cognitive batteries have been reported to be effective for predicting functional outcomes in patients with schizophrenia ( 7 ), the target domains are mainly executive aspects of cognition (i.e., attention, processing speed, and visual/verbal working memory). Higher order cognition, such as semantic memory, has received less attention, although disorganization of semantic memory has been considered as one of the intermediate cognitive phenotypes in patients with schizophrenia ( 8 ).…”
Section: Introductionmentioning
confidence: 99%